2013
DOI: 10.1080/09500693.2011.642324
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Cooperative Learning to Socio-scientific Discussion in Secondary School Science

Abstract: The aim of this research was to determine the benefits of cooperative learning to opening up socioscientific discussion in secondary science. Seventy-four classes of 20 13-14-year-old pupils in one secondary school were observed engaging in discussion concerning climate change over three rounds of action research involving 12 teachers associated with the implementation of a Topical Science strand of a new national science curriculum. Pupil views on the cooperative learning approach used to facilitate the lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…These findings underline the potential impact of visitor centre science in engaging the public in STEM learning, especially those who self-identify as non-scientists, to undertake STEM learning (Falk & Dierking, 2000). The nonscientists may participate despite having visited for purposes such as cultural entertainment, personal identification and historical reminiscence (Day & Bryce, 2013;Sheng & Chen, 2012). One potential disadvantage of contextualised STEM is that it risks causing processing overload, although there is no empirical evidence of this problem occurring at visitor centres (Fox, Park & Lang, 2007;Johnstone, 1991).…”
Section: Opportunities For Engagement With Stem Furnished By Visitor mentioning
confidence: 92%
“…These findings underline the potential impact of visitor centre science in engaging the public in STEM learning, especially those who self-identify as non-scientists, to undertake STEM learning (Falk & Dierking, 2000). The nonscientists may participate despite having visited for purposes such as cultural entertainment, personal identification and historical reminiscence (Day & Bryce, 2013;Sheng & Chen, 2012). One potential disadvantage of contextualised STEM is that it risks causing processing overload, although there is no empirical evidence of this problem occurring at visitor centres (Fox, Park & Lang, 2007;Johnstone, 1991).…”
Section: Opportunities For Engagement With Stem Furnished By Visitor mentioning
confidence: 92%
“…Most research on CL focuses on the effects of CL on academic achievements of elementary, secondary, high school and university students (Azap, 2012;Batdi, 2013;Çokparlamış, 2010;Çopur, 2011;Dilek, 2012;Kartal, 2014;Kartal ,2012;Tekeli, 2013;Tonbul, 2001). Very few of these investigate learner perceptions or teacher perceptions of collaborative learning ( Batdı,2013;Gillies and Boyle,2011; Gillies and Boyle,2010;;Kocaman,2005); Although scant, some research has focused on young learners' perceptions of CL (Lee and Macaro, 2013), whereas other research has focused on secondary (Day and Bryce, 2013;Gagne, 2013;Macquarrie, Howe andBoyle, 2012) or high school (Nair et al, 2012) students' perceptions of CL. Alghamdi and Gillies (2013) investigate male 10 th -grade students' perceptions of CL; Mulryon (1994) investigates 5 thand 6 th -grade students' perceptions of group work.…”
Section: Scope Of the Studymentioning
confidence: 99%
“…Research in the CL literature also supports this finding ( Kocaman, 2005) Similarly,the students reported that they prefered their groups to have three or more members. Day andBryce (2013, p.1537) indicate that a typical group may contain between two and six members, with four being the ideal number. , Lou, Abrami and d'Apollonia (2001) also find that students learned better in groups of three or four members.…”
Section: Group Compositionmentioning
confidence: 99%
“…Critical and creative thinking skills are more developed among the pupils in the experimental group compared to their counterparts as shown from their written works and performance tasks. Science education is in a unique position to help young people develop skills which should enable them to respond critically to various platforms such as media reports on issues with a science dimension (Day & Bryce, 2013). The teacher-implementer likewise realized that critical review of the AGHAMIC learning tasks using rubrics is also important to ensure the successful attainment of the learning outcomes.…”
Section: Reflections Of the Teacher-implementer In The Application Ofmentioning
confidence: 99%